Searching for authenticity - Baugh, S. Gayle; Sullivan, Sherry E., 1961- (Emerald Publishing Limited : Information Age Publishing Inc., 2015)
Volume 2 of the Research in Careers series focuses on the search for authenticity in one's career. Although there has been growing interest in the topic within the popular press, relatively little academic research has been completed on authenticity and careers. Researchers are still refining the concept of authenticity and are just beginning to investigate how it influences the enactment of careers in today's turbulent career landscape. This volume offers the first organized effort on the topic.
Keywords: Career development.; Quality of work life.; Job satisfaction.; Education -- Counseling -- Career Development.; Careers guidance.; elektronické knihy; electronic books